Lo spazio pubblico come luogo della frizione e della finzione. Pratiche artistiche e attiviste che confondono il reale. (Connessioni remote. Artivismo_Teatro_Tecnologia, 2021)
The aims of the text is to analyze activism as a form of complex relationship through those artistic practices which, making use of participatory approaches and performative actions, have questioned the role of public space. In particular, after having retraced the artistic critical debate regarding the autonomy of art and its ethical value through the argument between the two critics Claire Bishop and Grant Kester, the text proposes the analysis of two interventions that have re-discussed the public space in its logic of consensus and representation by working on the marginality of unrepresented and unrepresentable communities. The interventions that will be analyzed are: Art. 2 created by the Italian artist Adriana Torregrossa (Turin, 1999) and Bitte liebt Österreich created by the German artist Christop Schlingensief (Vienna, 2000). The two interventions in question will be analyzed in the light of the mechanism of unpredictability of the feedback loop, theorized by the scholar Erika Fischer-Lichte in her The Transformative Power of Performance (2004). The unpredictability is due to the impossibility of connecting a certain action to a direct consequence since the two levels - the performative one and the one of reality - are not openly declared, calling into question the viewer to become aware of his response based on the action framework he decides to follow.